Penerapan Model Problem Based Learning Berbantuan Video Animasi Untuk Meningkatkan Hasil Belajar Siswa Kelas VIII SMP Plus Noelbaki Pada Materi Relasi dan Fungsi - Lello, Mega Lita A; Nubatonis, Ofirenty E.; Nenohai, Juliana M. H. (Universitas Nusa Cendana, 2023)
This research was motivated by the low learning outcomes of students at SMP Reformasi Plus Noelbaki and the deficient of teacher creativity to design learning related to learning models and media that are appropriate to students' conditions. Therefore, this study aims to improve the learning outcomes of class VIII students of SMP Reformasi Plus Noelbaki in relation and function material through the application of the Problem Based Learning model assisted by video animation. This type of research is classroom action research which is carried out in two cycles and consists of four stages, namely planning, implementing, observing, and reflecting. Data collection techniques in this study were observation, tests, and documentation with the research instruments being test questions and observation sheets. Data analysis techniques are descriptive qualitative and quantitative. The results showed an increase in cycle I to cycle II, that were learning outcomes increased by 38.09% to 90.48%. The implementation of teacher observation increased from 66.67% to 78.82%. The results of observations on student activities increased from 62.5% in cycle I to 83.03% in cycle II. So that, it can be concluded that student learning outcomes increased after the implementation of the Problem Based Learning model assisted by animated videos at SMP Reformasi Plus Noelbaki